MANAJEMEN PENGEMBANGAN PENDIDIKAN ISLAM PERSPEKTIF AL-QUR’AN - Ahmad Zaki (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2021)
Management is the process of working together between individuals and groups as well as other resources in achieving organizational goals as a management activity. Management is a planning, Organizing, direction and supervision. Islamic management has two meanings, namely management as a science and management as an activity, namely management is bound by the rules of syara’, Islamic values. The basics of educational management in an Islamic perspective are, (1). Referring to credible and accurate literature. (2). Instilling sincerity in the educational process. (3). The first material taught to students is fundamental material. (4). Adhering to the scientific method by using the means of scientific thingking based on hujjah (valid evidence), through intensive and continuous search. (5). Making educational goals focused on the formation of a personal achievement. Efforts to develop Islamic education include: in the field of Islamic education infrastructure, namely: (1). Procurement of buildings. (2). Procurement of Islamic education facilities. In the field of Islamic education facilities, namely: (1). Improving the ability of educators. (2). Improving Islamic education methods. (3). Improvement of the content of Islamic education curriculum.